Perception of Agricultural Extension Agents Towards the Performance of Project-Based Extension Delivery on Food Security in Ghana - Jones Ebenenzer Osei; Enock Kwame Tham-Agyekum; Benjamin Sarfo-Mensah; Peter Kombat; Fred Ankuyi (International Journal on Food, Agriculture and Natural Resources, 2023)
Agricultural extension agents in Ghana's Upper East Region relied on project-based extension delivery services during the Covid-19 period. Using the perspectives of extension agents, this research looked at the effect of project-based extension delivery services on food security. A sample size of 144 agricultural extension agents from three distinct zones in the Region participated in this research, which used a descriptive correlation survey approach. Frequencies, percentages, means, standard deviation, correlation coefficients, and regression were used to analyse the data. In terms of effectiveness, efficiency, relevance, and economics, the project-based extension delivery service performed well. In terms of stability, food security was excellent. Food security and efficiency, relevance, and economics have a favorable and very significant association. Economy, efficiency, and age had 79% explanation for food security. On the perceived degree of food security, there was a substantial difference between male and female agricultural extension agents. The impact of project-based extension delivery services on food security was significant. The Ministry of Food and Agriculture should provide enough logistics, training, and incentive for agricultural extension agents to enhance information delivery.